Patterns of comorbidity and psychopharmacology in adults with intellectual disability and attention deficit hyperactivity disorder: an UK national cross-sectional audit. (24th May 2021) - Perera, Bhathika; Chen, John; Korb, Laura; Borakati, Aditya; Courtenay, Ken; Henley, William; Tromans, Sam; Shankar, Rohit
ABSTRACT: Background : Attention-deficit hyperactivity disorder (ADHD) is higher in people with intellectual disability (ID) compared to the general population. Available limited evidence suggests this population has increased psychological problems, diagnostic overshadowing and psychotropic prescribing. This audit Identifies and analyzes real-world characteristics, diagnostic practices, treatment, and management of ADHD in adults with ID. Research Design and Methods: Pooled retrospective case note data for people with ID and ADHD, collected from 30 organizations across the UK, were analyzed. Patients were classified into mild and moderate-profound ID groups. Associated mental health and neurodevelopmental co-morbidity, Demographics, concomitant psychotropics, and mental and behavioral concerns were collected. Group differences were reported using logistic regression models. Results: Of 445 participants, 73% had co-occurring autism spectrum disorder (ASD) and 65% were prescribed ADHD medications. Those on ADHD medication were less likely to be prescribed antipsychotics (p < 0.001) and antidepressants (p < 0.001). Multiple significant differences were found in ADHD medication response between ID groups and those with/without co-morbid ASD but not associated with challenging behavior reduction. Conclusions: High levels of neurodevelopmental and psychiatric comorbidity were found. ID severity and the presence of ASD appear to influence the use of certain psychotropic medications. Appropriate use of ADHD medication appears to reduce psychotropic polypharmacy.